Scheduled intermittent inotropes for Ambulatory Advanced Heart Failure. The RELEVANT-HF multicentre collaboration. (1st December 2018) - Oliva, Fabrizio; Perna, Enrico; Marini, Marco; Nassiacos, Daniele; Cirò, Antonio; Malfatto, Gabriella; Morandi, Fabrizio; Caico, Ivan; Perna, Gianpiero; Meloni, Sabina; Vincenzi, Antonella; Villani, Alessandra; et al.
Abstract: Background: Ambulatory Advanced Heart Failure (AAHF) is characterized by recurrent HF hospitalizations, escalating diuretic requirements, intolerance to neurohormonal antagonists, end-organ dysfunction, short-term reduced life expectancy despite optimal medical management (OMM). The role of intermittent inotropes in AAHF is unclear. The RELEVANT-HF registry was designed to obtain insight on the effectiveness and safety of compassionate scheduled repetitive 24-hour levosimendan infusions (LEVO) in AAHF patients. Methods: 185 AAHF NYHA class III–IV patients, with ≥2 HF hospitalizations/emergency visits in the previous 6 months and systolic dysfunction, were treated with LEVO at tailored doses (0.05–0.2 μg/kg/min) without prior bolus every 3–4 weeks. We compared data on HF hospitalizations (percent days spent in hospital, DIH) in the 6 months before and after treatment start. Results: Infusion-related adverse events occurred in 23 (12.4%) patients the commonest being ventricular arrhythmias (16, 8.6%). During follow-up, 37 patients (20%) required for clinical instability treatment adjustments (decreases in infusion dose, rate of infusion or interval). From the 6 months before to the 6 months after treatment start we found lower DIH (9.4 (8.2) % vs 2.8 (6.6) %, p < 0.0001), cumulative number (1.3 (0.6) vs 1.8 (0.8), p = 0.0001) and length of HF admissions (17.4 (15.6) vs 21.6 (13.4) days, p = 0.0001). One-year survival was 86% overall and 78% free from death/LVAD/urgent transplant. Conclusions: In AAHF patients, who remain symptomatic despite OMM, LEVO is well tolerated and associated with lower overall length of hospital stay during six months. This multicentre clinical experience underscores the need for a randomized controlled trial of LEVO impact on outcomes in AAHF patients. Highlights: In ambulatory advanced HF patients repetitive levosimendan is well tolerated. Repetitive levosimendan is associated with lower time spent in hospital during 6 months. This treatment might represent a window of opportunity before resorting to LVAD. Controlled data on outcomes associated with repetitive levosimendan use are needed.